A novel process intensification strategy for second-generation ethanol production from sugarcane bagasse in fluidized bed reactor. (August 2018) - Antunes, F.A.F.; Chandel, A.K.; Brumano, L.P.; Terán Hilares, R.; Peres, G.F.D.; Ayabe, L.E.S.; Sorato, V.S.; Santos, J.R.; Santos, J.C.; Da Silva, S.S.
Abstract: Due to forthcoming scarcity of fossil fuels and serious environmental concerns, concerted efforts are required to develop the intensified and robust ethanol production from renewable sources. Currently, lignocellulosic materials are among the main available renewable carbon source in the world. Within this context, we present a novel proposal of intensification of the process for second generation (2G) ethanol production from sugarcane bagasse (SCB) employing fluidized bed reactor. Successive steps of SCB i.e. alkaline pre-treatment, saccharification and fermentation to ethanol were carried out in a same column reactor without opening it during the entire process. In the alkaline pretreatment process, a 2 2 full factorial design of experiments was designed and executed to evaluate the effect of NaOH concentration (from 0.1 to 0.5 M) and time (from 1 to 4 h) on the enzymatic digestibility of pretreated biomass. Enzymatic hydrolysis yielded glucose and xylose of around 87% and 43%, were achieved, respectively, in saccharification step, when used alkaline pre-treated biomass conducted in process by using variables in high level. Thus, Simultaneous saccharification and co-fermentation (SSCF) were performed by using the wild xylose and glucose fermenting yeast Scheffersomyces shehatae UFMG-HM 52.2, verifying ethanol yield and productivity of 0.34 g/g and 0.18 g L/h, respectively. Results showed the potential of using fluidized bed reactor for ethanol production under different process conditions, reducing equipments and process costs with mass transference. Graphical abstract: